(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Introduction: Vision plays a critical role in maintaining quality of life, particularly among elderly individuals. Senile cataracts, a leading cause of visual impairment in older adults, can significantly hinder daily functioning and vision-related quality of life (VRQL). Although phacoemulsification surgery is the standard treatment, its broader impact on functional independence and VRQL warrants further exploration. Purpose: This study aimed to evaluate changes in activities of daily living (ADL) and VRQL in patients with senile cataracts before and after undergoing phacoemulsification surgery. Methods: An analytic cross-sectional study was conducted using purposive randomized sampling. ADL was assessed using the Barthel Index, while VRQL was measured using the National Eye Institute Visual Function Questionnaire-25 (NEI-VFQ-25). The Marginal Homogeneity test was applied to analyze changes in ADL, and the Wilcoxon test was used to analyze VRQL data. Results: The study included 50 patients with a mean age of 65.9 ± 9.6 years, of whom 42% were male and 58% female. Of the participants, 58% had immature cataracts, and 42% had mature cataracts. There was a significant improvement in ADL post-surgery (p = 0.000). Preoperatively, 50% of the patients were severely dependent, 40% were moderately dependent, and 10% were mildly dependent. Postoperatively, 82% of the patients became independent, 14% mildly dependent and 4% moderately dependent. VRQL also showed significant improvements across domains, including overall function, visual acuity, near vision, distance vision, and color vision (p = 0.000). Conclusion: Phacoemulsification surgery in patients with senile cataract significantly enhances both functional independence in daily living and vision-related quality of life.